2017
DOI: 10.1371/journal.pone.0178413
|View full text |Cite
|
Sign up to set email alerts
|

Proponent or collaborative: Physician perspectives and approaches to disease modifying therapies in sickle cell disease

Abstract: Sickle cell disease (SCD) is an inherited blood disorder that primarily affects African-American and other ethnic minority populations. There are three available disease-modifying therapies for sickle cell disease: hydroxyurea (HU), bone marrow transplantation (BMT), and chronic blood transfusion (CBT). Since these treatments vary in their therapeutic intent, efficacy in preventing progression of the disease, short and long-term adverse effects, costs and patient burden, the decision-making process regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 33 publications
(36 reference statements)
1
51
0
1
Order By: Relevance
“…Another reason may be the increased availability of clinical drug trials and other investigational therapies for SCD at University‐based practices. In some cases, rather than discussing HCT as a treatment option, in a child with minimal SCD‐related complications, traditional therapy with hydroxyurea or enrolment in clinical drug trials may be preferred over referral for HCT (Bakshi et al , ). Additionally, with gene editing therapies also on the horizon, University‐based providers, who tend to have greater access to advanced therapies, may prefer to await the opportunity to potentially refer a patient for gene editing in the future, rather than to have them undergo HCT (Ribeil et al , ; Bueren et al , ; Ikawa et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason may be the increased availability of clinical drug trials and other investigational therapies for SCD at University‐based practices. In some cases, rather than discussing HCT as a treatment option, in a child with minimal SCD‐related complications, traditional therapy with hydroxyurea or enrolment in clinical drug trials may be preferred over referral for HCT (Bakshi et al , ). Additionally, with gene editing therapies also on the horizon, University‐based providers, who tend to have greater access to advanced therapies, may prefer to await the opportunity to potentially refer a patient for gene editing in the future, rather than to have them undergo HCT (Ribeil et al , ; Bueren et al , ; Ikawa et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Sociocultural factors, both patient-and provider-related, may also contribute to this phenomenon (Gluckman et al, 2017). Studies assessing medical decision-makers' role in this trend show that parents of children with SCD and adult patients affected by the disease are willing to accept relatively high risk of mortality to achieve cure of the disease (Van Besien et al, 2001;Hansbury et al, 2012;Meier et al, 2015). Research on clinicians' perspectives of HCT as treatment for SCD suggests a lower tolerance of risk in order to achieve cure among the healthcare providers who treat this population (Van Besien et al, 2001;Bakshi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with haemoglobin disorders, such as SCD, experience a wide range of complications that have severe implications, not only for the individuals themselves, but also for their families (Anie, 2005;Bakshi et al, 2017;Brown, Weisberg, & Sledge, 2016). Thus, multidisciplinary and comprehensive interventions are considered vital in order to effectively manage SCD and its complications.…”
Section: 1mentioning
confidence: 99%
“…It has also been found that physicians have varied approaches to decision making regarding disease modifying therapy for SCD (Bakshi et al, 2017). The research of these authors identified two approaches the first of which was termed collaborative where all treatment options were discussed and patient and family were equipped to make informed decisions.…”
Section: Shaping a Reality Around Sickle Cell Disorder 82mentioning
confidence: 99%
See 1 more Smart Citation